Perception of university students on the role of educational digital stimuli in achieving academic passion in vocational education - K. S. Aljedayah; A. M. Al-Duwairi; M. A. K. Al-Momani; M. M. Al-Mzary; M. O. Al-Momani; G. S. Khataybeh; A. S. Al-Abed Rhman (Образование и наука)
Introduction. Digital stimuli are one of the strategies prepared by higher education institutions in university teaching in the field of vocational education, but they do not attach importance to them from other strategies that are used. The investigation of the role of educational digital stimuli in achieving the academic passion of vocational education students in Jordanian universities in light of COVID-19 is important to try to know the effect of digital stimuli on the academic passion of vocational education students.   Methodology and research methods. The descriptive survey method was used to analyse the data. To achieve the objectives of the study, a questionnaire consisting of (29) items was designed, divided into three areas: dynamics (11 items), mechanics (7 items), and components (11 items) to collect data. The study sample consisted of 260 male and female students in Jordanian universities.   Results and scientific novelty. The results showed that the role of educational digital stimuli in achieving academic passion was ‘high’ with no statistically significant differences due to the gender variable, with statistically significant differences due to the variables of the academic year and university type.   Practical significance. The study recommends designing educational environments that are attractive, interactive, and related to the students’ reality, using strategies for deep information processing, problem-solving method, creativity and critical thinking in order to achieve students’ involvement in learning.